On-Farm Multilocation Adaptability Trial of Promising Rice Genotypes across Manipur - S, Bhuvaneswari; I, Meghachandra Singh; Kumar, Sudhir; S, Sumangal Singh; LeendaMonsang, Ts.; Sharma, Susheel Kumar; Singh, Gunamani; N, Prakash (Indian Journal of Hill Farming, 2018)
An on-farm multilocational trial was conducted at farmersâ€™ fields in five districts of Manipur state during kharif, 2015 to test the adaptability of two promising advanced breeding lines of rice (RCM-30 & RCM-31) along with two check varieties (CAU R1 & RC Maniphou-10). Pooled analysis of variance for plot yield reflected existence of significant Varietal, Location and Variety Ã— Location interaction suggesting diversity in the testing environments. Rice genotype RCM-30 showed highest yield (51.1 kgs/64 m2plot) followed by RCM-31(48.9 kgs/plot). Also, the stability parameter, Vi 2 was nonsignificant for RCM-30 combined with lowest Mean deviation (Di) depicting the superiority over checks as the most adapted genotype under diverse range of environments.